APPLICATION OF THE TPACK APPROACH THE PPKn MODULE TO IMPROVE CONCEPT UNDERSTANDING - Widjajanti, Sri; Rufi’i; Suhari (JTP - Jurnal Teknologi Pendidikan, 2021)
This research was conducted to develop a TPACK-based module (Technological Pedagogical and Content Knowledge) to support the development of students' concept knowledge in PPKn (Pancasila and civic education) online learning for grade 7th. The development of the module adopts the steps of the ADDIE model. To test the feasibility level of the module, material experts, learning design experts, teachers and students as users of the product were tested. To measure effectiveness of TPACK module to develop students' concept knowledge, paired t-test is adopted. The results of data analysis show that the learning module developed has a very high level of feasibility, namely according to material experts 95.8%, learning design experts 82.4%, teachers 97.2%, students in individual trials 90.8%, small group validation 92.6% and field validation 88.1%.